Factors Affecting Second Language Acquisition: - Mohammed, Mrs. Sumaya J. Alhaj (Aljameai, 2022)
Abstract: This paper focuses on some factors which affect second language acquisition (SLA), e.g: learner’s age, personality, motivation, etc. The paper is a critical review that presents some authors opinions and arguments which supported the main idea of the paper. In addition, two non-native English learners are chosen as case studies. They are from different mother tongue. Both of them are interviewed in order to collect data, then the data is analyzed according to the factors which are mentioned earlier. The analysis had got a great role in supporting the idea of the paper which is concentrating in how learner influenced by some factors. الملخص: تركز الدراسة في هده الورقة البحثية على بعض العوامل التي تؤثر في اكتساب اللغة الثانية والتي من ضمنها: العمر, الشخصية, الحافز للتعلم، إلخ .هده الورقة عبارة عن دراسة نقدية لعرض بعض آراء نقاشات الكتاب والتي كان لها دور في دعم الفكرة الأساسية للبحث . كما تم اختيار شخصين من غير الناطقين باللغة الانجليزية كعينة للدراسة. كلاهما يتحدث لغة مختلفة عن الاخر. وقد تم إجراء مقابلة معهما لجمع المعلومات. وتم تحليل هده المعلومات وفقا لتلك العوامل التي تم دكرها مسبقا. وكان لتحليل هده المعلومات دور كبير في دعم الفكرة التي ترتكز عليها هده الورقة البحثية.